Answer:
y - 1 = -2 (x + 1)
Step-by-step explanation:
point slope form: (y - y1) = m (x - x1)
m is the slope. To find m the formula is:
(y2 - y1) / (x2 - x1)
The given ordered pairs are: (-1,1) and (4,-9)
y2 is the y in the second ordered pair (-9)
y1 is y in the first ordered pair (1)
x2 is x in the second ordered pair (4)
x1 is x in the first ordered pair (-1)
= (-9 - 1) / (4 +1)
= -10/5
m = -2
Now plug m (-2), y1 (1), and x1 (-1) into the point slope form
y - 1 = -2 (x - -1)
y - 1 = -2 (x + 1)